Enhancing Potential of Trimethylamine Oxide on Atmospheric Particle Formation - Nanna Myllys; Tuomo Ponkkonen; Sabrina Chee; James Smith (Atmosphere, 2019)
The role of an oxidation product of trimethylamine, trimethylamine oxide, in atmospheric particle formation is studied using quantum chemical methods and cluster formation simulations. Molecular-level cluster formation mechanisms are resolved, and theoretical results on particle formation are confirmed with mass spectrometer measurements. Trimethylamine oxide is capable of forming only one hydrogen bond with sulfuric acid, but unlike amines, trimethylamine oxide can form stable clusters via ion−dipole interactions. That is because of its zwitterionic structure, which causes a high dipole moment. Cluster growth occurs close to the acid:base ratio of 1:1, which is the same as for other monoprotic bases. Enhancement potential of trimethylamine oxide in particle formation is much higher than that of dimethylamine, but lower compared to guanidine. Therefore, at relatively low concentrations and high temperatures, guanidine and trimethylamine oxide may dominate particle formation events over amines.